Manajemen 5S dalam Kinerja Lembaga Pendidikan - Rosita Endang Kusmaryani (Dinamika Pendidikan, 2008)
Education  institute  is  a  organization  having  import ant  role  in giving quality of education service, what as a whole holding responsible' yield quality of human resource. In education service management required by correct handling and checking, but which often happened is existence of human errors which be not parried. The mistake of man 'even affect at education institute performance in executing education serviceHuman errors  actually can be eliminated if job  process  can be designed in such a manner by paying attention to man factors and work environment.  In  reaching  the  education  management  efficiency,  5S management  as first step a management. 5S  management   is' a approach  giving  pressure  at  workplace organizing better. It is because basically resulted from by 'mistakes is man, besides coming from itself man also resulted from the work enviroument.   Key  words  : 5S management,     performance